2018
DOI: 10.1007/s13224-018-1157-x
|View full text |Cite
|
Sign up to set email alerts
|

One-Year Follow-Up of Women with Severe Acute Maternal Morbidity (SAMM): A Cohort Study

Abstract: Background Some women experience unforeseen complications during pregnancy and childbirth, which may be life threatening; their survival depends on intensive support and timely interventions. The aim of this study was to assess the long-term prevalence of adverse health conditions and their impact on quality of life in women who had severe acute maternal morbidity (SAMM). Methods This is a prospective cohort study comprising 43 women with SAMM during 2015 (exposure group) and 43 women who had an uneventful pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…A total of 31 558 women were enrolled in the studies. In eight studies, the population age was reported as a mean ranging between 25.3 and 27.7 for MNM, 25.6 and 27.5 for no MNM, 11,14,23 and 25.6 and 28.0 for joint mean 10,12,16,17,22 . The remaining seven studies reported age as an interval between ≤19 and ≥40 9,13,15,18–21 .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 31 558 women were enrolled in the studies. In eight studies, the population age was reported as a mean ranging between 25.3 and 27.7 for MNM, 25.6 and 27.5 for no MNM, 11,14,23 and 25.6 and 28.0 for joint mean 10,12,16,17,22 . The remaining seven studies reported age as an interval between ≤19 and ≥40 9,13,15,18–21 .…”
Section: Resultsmentioning
confidence: 99%
“…When looking at various aspects of MNM, it was found that MNM was negatively associated with mental health. A significant proportion of the studies demonstrated an increased risk of suicidal thoughts, depression and increased risk of other psychiatric conditions 14–17,21–23 . However, the methodological heterogeneity in these studies, including different duration of follow‐up and different endpoint measures, makes it difficult to compare the studies directly.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations